Therapeutic Efficacy of a Trichinella Spiralis Paramyosin-Derived Peptide Modified With a Membrane-Targeting Signal in Mice With Antigen-Induced Arthritis - Chen, Yi; Shao, Shuai; Huang, Jingjing; Gu, Yuan; Cheng, Yuli; Zhu, Xinping (Frontiers in Microbiology, 2020)
Helminth-derived molecules have the ability to modulate the host immune system. Our previous study identified a tetradecapeptide derived from Trichinella spiralis paramyosin (Ts-pmy) that could bind to human complement component C9 to inhibit its polymerization, making the peptide a candidate therapeutic agent for complement-related immune disorders. Here, the peptide underwent an N-terminal modification with a membrane-targeting signal (a unique myristoylated peptide) to improve its therapeutic efficacy. We found that the modified peptide had a binding affinity to human C9 that was similar to that of the original peptide, as confirmed by microscale thermophoresis assays. The binding of the modified peptide to human C9 resulted in the inhibition of C9-related complement activation, as reflected by the decreased Zn2+-induced C9 polymerization and the decreased C9-dependent lysis of rabbit erythrocytes. In addition, the original and modified peptides could both bind to recombinant mouse C9 and inhibit the C9-dependent lysis of rabbit erythrocytes in normal mouse serum (NMS), which meant that the peptides could cross the species barrier to inhibit complement activity in mice. Further in vitro and in vivo analyses confirmed that the peptide modification increased the retention time of the peptide. Furthermore, intraarticular injection of the modified peptide markedly ameliorated knee swelling and joint damage in mice with antigen-induced arthritis (AIA), as assessed histologically. These results suggested that the Ts-pmy-derived peptide modified with a membrane-targeting signal was a reasonable candidate therapeutic agent for membrane attack complex (MAC)-related diseases (such as RA) and the study presented a new modification method to improve the potential therapeutic effects of the peptide.